A very very very dark matter - McDonagh, Martin 1970- (Faber and Faber Limited, 2018)
"In a townhouse in Copenhagen works Hans Christian Andersen, a teller of exquisite and fantastic tales beloved by millions. But the true source of his stories dwells in his attic upstairs, her existence a dark secret kept from the outside world. Dangerous, twisted and funny, Martin McDonagh's new play travels deep into the abysses of the imagination"--
A Very Very Very Dark Matter was first performed at the Bridge Theatre, London, on 12 October 2018
Keywords: Andersen, H. C. / (Hans Christian) / 1805-1875 / Drama; Prisons / Drama; Andersen, H. C. / (Hans Christian) / 1805-1875; Prisons; Drama